Morphological characterization and grouping of chickpea (Cicer arietinum) genotypes for drought tolerance - KUMAR, TAPAN; BHARADWAJ, C; TIWARI, NEHA; SATYAVATHI, C TARA; PATIL, B S; SARKER, ASHUTOSH; ALAM, AFROZ (The Indian Journal of Agricultural Sciences, 2018)
Fifty genotypes of chickpea (Cicer arietinum L.) were evaluated to estimate for drought tolerance as well as genetic variability among the selected chickpea genotypes for quantitative characters under normal and drought conditions. A significant variation was observed for control and drought treatments for most of the investigated characters. Under moisture stress treatment, there was sufficient decrease in the mean of most of the characters under study. The two way analysis of variance was carried out for all the characters for irrigated and under drought. The mean sum of square was highly significant for all the characters under study indicating significant variability in the materials. The analysisof variance for irrigated and drought conditions revealed that the differences among the genotypes were significant. The mean sum of square was highly significant for all the characters. Pusa 1103 and Pusa 362 were the most tolerant along with ICC 4958 which is a well-known donor for the drought tolerance.